Assessment and management of seafood safety and quality : current practices and emerging Issues - Ryder, J.; Karunasagar, I.; Ababouch, Lahsen (Rome F A O, 2014)
This technical paper compiles the state of knowledge on seafood safety and quality with the aim to provide a succinct yet comprehensive resource book to seafood quality and safety managers, including topics on emerging issues such as new pathogens, the impact of climate change on seafood safety, and the changing regulatory framework. After introductory chapters about world fish production, trade, consumption and nutrition, and about the developments in safety and quality systems, the technical paper devotes a chapter to a detailed review of the hazards causing public health concerns in fish and fish products, covering biological (pathogenic bacteria, histamine, viruses, parasites and biotoxins), chemical (veterinary drugs, industrial organic contaminants, environmental inorganic contaminants and allergens) and physical hazards. This is followed by a chapter on seafood spoilage and quality issues, while a further chapter covers the likely impact of climate change on seafood safety. The latter chapter focuses on impacts on microbiological safety and on harmful algal blooms. A further chapter provides a detailed coverage of the implementation and certification of seafood safety systems covering risk mitigation and management tools, with a detailed description of the requirements for the implementation of: good hygiene practices and good manufacturing practices; the Hazard Analysis and Critical Control Points (HACCP) system; and the monitoring programmes to control biotoxins, pathogenic bacteria and viruses and chemical pollutants. It concludes with a section on private labelling and certification schemes. The subsequent chapter details the international framework, covering the World Trade Organization, the Codex Alimentarius Commission, the FAO Code of Conduct for Responsible Fisheries, and the World Organisation for Animal Health. It then presents the regulatory frameworks governing seafood trade in the European Union (Member Organization), the United States of America, Japan, Australia and New Zealand. --Page v.
Keywords: Seafood industry--Quality control; Fishery products--Quality control; Fishery processing--Quality control; Fishery products--Spoilage.; Seafood--Contamination.; Seafood--Evaluation.; Fishery processing--Quality contro; Fishery products--Quality control; Fishery products--Spoilage.; Seafood--Contamination.; Seafood--Evaluation.; Seafood industry--Quality control